Natural killer cells in the human lung tumor microenvironment display immune inhibitory functions - Diane Damotte; Laurence Zitvogel; Marco Alifano; Marie-Caroline Dieu-Nosjean; Gabriela Bindea; Jeremy Goc; Jules Russick; Pierre-Emmanuel Joubert; Mélanie Gillard-Bocquet; Carine Torset; Maxime Meylan; Florent Petitprez; et al. (Journal for ImmunoTherapy of Cancer)
Background Natural killer (NK) cells play a crucial role in tumor immunosurveillance through their cytotoxic effector functions and their capacity to interact with other immune cells to build a coordinated antitumor immune response. Emerging data reveal NK cell dysfunction within the tumor microenvironment (TME) through checkpoint inhibitory molecules associated with a regulatory phenotype.Objective We aimed at analyzing the gene expression profile of intratumoral NK cells compared with non-tumorous NK cells, and to characterize their inhibitory function in the TME.Methods NK cells were sorted from human lung tumor tissue and compared with non- tumoral distant lungs.Results In the current study, we identify a unique gene signature of NK cell dysfunction in human non-small cell lung carcinoma (NSCLC). First, transcriptomic analysis reveals significant changes related to migratory pattern with a downregulation of sphingosine-1-phosphate receptor 1 (S1PR1) and CX3C chemokine receptor 1 (CX3CR1) and overexpression of C-X-C chemokine receptor type 5 (CXCR5) and C-X-C chemokine receptor type 6 (CXCR6). Second, cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and killer cell lectin like receptor (KLRC1) inhibitory molecules were increased in intratumoral NK cells, and CTLA-4 blockade could partially restore MHC class II level on dendritic cell (DC) that was impaired during the DCs/NK cell cross talk. Finally, NK cell density impacts the positive prognostic value of CD8+ T cells in NSCLC.Conclusions These findings demonstrate novel molecular cues associated with NK cell inhibitory functions in NSCLC.